EPR investigation of electronic excitations in rare gas solids (Review Article): - Zhitnikov, R. A.; Dmitriev, Yu. A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1998)
The methods are described for producing unstable paramagnetic excited states in rare gas cryocrystals Ne, Ar, Kr, and Xe through the trapping, in the cryocrystals growing from the gas phase, the products of the gas discharge taking place in the same or other rare gas. The paper presents a technique and results of an observation and investigation of excited states in rare gas cryocrystals with electron paramagnetic resonance (EPR). The discovered unstable paramagnetic centers are interpreted as being local metastable excited np5(n+1)s atomic-type states in rare gas cryocrystals which are subject to the action of the anisotropic electric field resulted from the crystal surroundings distorted by the center. An account is given of the mechanisms for formation of observed paramagnetic excited states in cryocrystals which arise owing to the excitation energy of the metastable 5P2 atoms of Ne, Ar, Kr, Xe and He 23S1 and 21S0 atoms that form in the discharge in an appropriate gas and trap in the growing cryocrystal.